Komposisi dan Tingkat Kerusakan Vegetasi Hutan Mangrove di Kecamatan Sukadana Kabupaten Kayong Utara Provinsi Kalimantan Barat - Riza Linda, Febrry Harnanda, Rafdinal (Universitas Tanjungpura, 2018)
Mangrove forests grow on tropical coasts or embouchures with soft soils and are flooded by the tide. The purpose of this study was to investigate composition and destruction level of Mangrove forests vegetation in Sukadana Sub-District of Kayong Utara Regency. The sample was taken on June 2017 by employing single plot method. The findings indicate that at the time of sampling and adult, 7 types of mangrove vegetation are identified, specifically Acanthus ilicifolius, Acrostichum speciosum, Avicennia alba, Bruguiera gymnorrhiza, Rhizophora apiculata, Ceriops decandra and Xylocarpus granatum are discovered at mangrove forests in Sukadana Sub-District of Kayong Utara Regency. The highest density of 780 trees/ha. Is found at Sutera Village at the stake phase and the lowest density of 128 trees/ha is located in the tree phase in Sejahtera Village. Diversity index (H’) of mangrove forest vegetation in Sukadana Sub-district is categorized as low to average (H’ = 0.57-1.28). Based on the total density of less than 1000 and the relative closure of less than 50% of the trees, therefore the extent of damage to mangrove forest vegetation in Kecamatan Sukadana Kayong Utara District is categorized as initial damage.